2013
DOI: 10.1101/lm.030825.113
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormone (20-hydroxyecdysone) modulates the acquisition of aversive olfactory memories in pollen forager honeybees

Abstract: Here, we examine effects of the steroid hormone, 20-hydroxyecdysone (20-E), on associative olfactory learning in the honeybee, Apis mellifera. 20-E impaired the bees' ability to associate odors with punishment during aversive conditioning, but did not interfere with their ability to associate odors with a food reward (appetitive learning). The steroid had a significant impact also on the expression of amine-receptor genes in centers of the brain involved in the formation and recall of associative olfactory mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…The discovery that male-transferred 20E is a key regulator of female reproductive biology in An. gambiae adds to the myriad of effects that this hormone exerts on insect adult physiology (2,3,(17)(18)(19)(20)(21)(22)(23). Interestingly, the steady decline of 20E levels in the atrium during the first day after copulation (17) is reminiscent of the process of mating plug digestion, which is completed in a similar time frame (5)(6)(7)16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery that male-transferred 20E is a key regulator of female reproductive biology in An. gambiae adds to the myriad of effects that this hormone exerts on insect adult physiology (2,3,(17)(18)(19)(20)(21)(22)(23). Interestingly, the steady decline of 20E levels in the atrium during the first day after copulation (17) is reminiscent of the process of mating plug digestion, which is completed in a similar time frame (5)(6)(7)16).…”
Section: Discussionmentioning
confidence: 99%
“…This hormone has been found to affect multiple aspects of adult insect physiology: It controls lifespan (19), learning (20), stress-induced responses (21), sleep regulation, and social interactions (22). Moreover 20E acts as a sexual hormone, influencing male sexual behavior in Drosophila (23).…”
Section: Significancementioning
confidence: 99%
“…The lack of specific pharmacological blockers of these receptors has until now precluded straightforward analyses of their role in aversive learning. Impairment of aversive learning yields conflicting evidence with respect to this topic: while pharmacological blocking with vertebrate antagonists indicated that AmDOP2 receptors are necessary for aversive learning (Vergoz et al, 2007a), analyses of transcript levels of dopaminergic receptor genes suggested that impairment of aversive learning is associated with an increase of AmDOP2 receptors (Geddes et al, 2013). More experiments are necessary to elucidate whether and how these different receptors contribute to aversive learning.…”
Section: The Neural Basis Of Aversive Learning: Us Signalingmentioning
confidence: 99%
“…An interesting twist to the study of aversive learning and dopaminergic signaling is the discovery that 20-hydroxyecdisone (20E), a metabolite of the steroid hormone ecdysone, which intervenes in insect development and reproduction (Riddiford et al, 2000), impairs aversive but not appetitive conditioning in bees (Geddes et al, 2013). This impairment seems to be achieved in part via the dopamine/ecdysone receptor gene AmGPCR19, which is the honeybee ortholog of the dopamine/ecdysone receptor gene 48 (DmDopEcR) identified in Drosophila (Srivastava et al, 2005).…”
Section: The Neural Basis Of Aversive Learning: Us Signalingmentioning
confidence: 99%
“…Insects, the most diverse group of invertebrates, also serve as useful models for studying higher CNS functions because of the simplicity of their nervous system, their amenability to genetic approaches, and the availability of established learning paradigms (Heisenberg, 2003;Mizunami et al, 2004;Giurfa, 2013). The best-known experimental paradigm for learning and memory in insects is olfactory associative conditioning in honeybees, in which bees associate a specific odor presented as a CS in a training session, with a reward (usually sucrose solution) presented as a US (Takeda, 1961;Bitterman et al, 1983;Menzel, 2012;Geddes et al, 2013;Scheiner et al, 2013). Since honeybees have the most prominent learning and memory capacity among insect species, this paradigm has frequently been used as a model system to explore their behavioral and physiological mechanisms (Sandoz, 2011;Menzel, 2012;Scheiner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%